The Correlation between Eating Patterns and Sedentary Activity with Obesity in Adolescents at Labschool UNESA 2 Middle School - Maulidina Putri Azzahra; Rahayu Dewi Soeyono (Jurnal Gizi dan Kesehatan Nusantara, 2026)
Adolescent obesity is a nutritional problem that continues to increase the risk of various health problems in adulthood. An unbalanced eating pattern and high levels of sedentary activity are believed to be associated with the development of obesity among adolescents. This study aimed to determine the correlation between eating patterns and sedentary activity with obesity in adolescents at Labschool UNESA 2 Middle School. This study employed a quantitative cross-sectional design. The research sample consisted of 60 respondents. Sampling was initiated by screening the nutritional status of the entire population, followed by a staged sampling technique, using total sampling for obese respondents and simple random sampling for non-obese respondents. Data were collected using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), the Adolescent Sedentary Activity Questionnaire (ASAQ), and measurements of body weight and height. Data analysis was conducted using the Spearman Rank correlation test. The results showed that meal frequency (p=0.010; r=0.329) and total energy intake (p=0.029; r=0,282) were significantly associated with obesity in adolescents at Labschool UNESA 2 Middle School. Meanwhile, protein, fat, and carbohydrate intake, as well as sedentary activity, were not significantly associated with obesity. The result showed that obesity among adolescent at Labschool UNESA 2 Middle School was more closely related to meal frequency and total energy intake than to individual macronutrient intake or sedentary activity.